Tina [videorecording (DVD)] - Turner, Tina; Bassett, Angela; Winfrey, Oprah; Loder, Kurt; Hall, Katori (Warner Bros. Entertainment, 2021)
Profiles the life and career of Tina Turner, featuring her personal reflections, archival interviews, and contributions from others.